World wide web business catalogs in business-to-business procurement - Archer, Norman P.; McMaster University, Michael G. DeGroote School of Business (My University, 1999)
The use of on-line Web catalog systems to support business-to-business procurement activities is a rapidly growing function in electronic commerce. These systems can be used to link suppliers to customers in different ways, with a variety of support functions and with several different information architectures: many-to-one, one-to-many, and many-to-many suppliers-to customers respectively. In addition, approaches differ among the types of products and services (P/S) being exchanged: production P/S, maintenance, repair and operations (MRO), and capital, R&D, and ad hoe procurement. There will also be differences that depend upon whether the P/S are to be requisitioned or sourced. This paper explores the various issues that affect decisions among the different procurement architectures. We conclude that, although large supplier and customer companies may wish to support their own one-to-many and many-to-one procurement architectures respectively for reasons of flexibility and economies of scale, small to medium companies will probably find that the most cost-effective approach is a many-to-many architecture that is converted into a many-to-one-to-many architecture through a central multi catalog intermediary.
26 leaves : ; Includes bibliographical references (leaves 21-22). ; "March, 1999".
Keywords: Electronic commerce World Wide Web Commercial catalogs Industrial marketing Purchasing Industrial procurement